Substance use during pregnancy: the role of mindfulness in reducing stigma - Shank, Taylor M.; Tjahaja, Surja; Rutter, Tara M.; Mackiewicz Seghete, Kristen L. (Frontiers in Psychology, 2024)
Stigmatization is a significant healthcare barrier among individuals who utilize substances during pregnancy. Of the 3.6 million U.S. births each year, approximately 10% are affected by perinatal substance use, an estimate which is likely underestimated due to fear of stigma and prosecution. Of those experiencing perinatal substance use, less than 11% receive treatment, while maternal deaths due to overdose during the postpartum period have increased by 81% from 2017-2020. Societal perception of non-pregnant individuals experiencing substance use disorders recognizes the biological basis of addiction, whereas for pregnant individuals, societal perception slides into moral failing as the basis of addiction. Many recommendations and guidelines for decreasing substance use stigmatization among non-pregnant and pregnant individuals exist. We focus on the use of mindfulness in recognizing and addressing structural and social stigma within healthcare systems. Mindfulness has been extracted from its roots as an essential element of the Eightfold Path in Buddhism, which largely centers on living ethically to reduce suffering of self and others. By acknowledging the roots of mindfulness, providers can engage mindfully in practices that help identify one’s overarching personal values and encourage one to lead healthcare encounters compassion and willingness to support help-seeking community members who are experiencing suffering. A deeper awareness of mindfulness practices within the context of ethical conduct can support healthcare shifts away from criminalization toward more patient- and family-centered approaches.